Factors Influencing Customers’ Decisions To Hajj Saving Products In Bank Syariah Indonesia During The Covid-19 Pandemic - Mardhiyaturrositaningsih Mardhiyaturrositaningsih; Dimas Martha Alif (JPS (Jurnal Perbankan Syariah), 2022)
This research aims to show the influence of brand image, trust, and promotion on customers’ decisions to use Bank Syariah Indonesia Hajj savings during the covid-19 pandemic. The population of this research is the customers of Hajj savings of Bank Syariah Indonesia branch office of MT Haryono, as many as 550 people. Sampling used a random side technique with a Slovin approach to obtain a sample of 100 people. They are collecting data using primary data, namely questionnaires. Data analysis was carried out by testing validity, reliability, classical assumption, and hypothesis testing. The results of this study indicate that brand image and trust do not affect customers’ decisions in using Bank Syariah Indonesia Hajj savings during the covid-19 pandemic. Promotions positively affect customers’ decisions in using Bank Syariah Indonesia Hajj savings during the covid-19 pandemic. This research can complement the existing theory and become a reference for Bank Syariah Indonesia to improve the promotion strategy of Hajj savings products.